Canadian Adolescents' Experiences of Dating Violence: Associations with Social Power Imbalances. Issue 1 (January 2023) - Exner-Cortens, Deinera; Baker, Elizabeth; Craig, Wendy
A substantial minority of adolescents experience and use dating violence in their sexual and/or romantic relationships. Limited attention has been paid to exploring theory-driven questions about use and experience of adolescent dating violence (ADV), restricting knowledge about promising prevention targets for diverse groups of youth. To address this gap, this paper investigates whether factors tied to power imbalances (bullying, risk of social marginalization) are associated with patterns of ADV victimization and perpetration in a large sample of Canadian mid-adolescents. We used data from the 2017/2018 Health-Behavior in School-Aged Children (HBSC) study, a nationally representative sample of Canadian youth. Our study was comprised of adolescents who were in grades 9 or 10, and who had dated in the past 12 months (N = 3779). We assessed multiple forms of ADV and bullying victimization and perpetration. We also included six variables assessing adolescents' risk of social marginalization: gender, race/ethnicity, immigration status, family structure, food insecurity, and family affluence. We used latent class analysis to explore the ways adolescents experience and use different forms of ADV, and then examined whether factors tied to power imbalances (bullying, social marginalization) were associated with classes of ADV. Three ADV classes emerged in our sample: uninvolved (65.7%), psychological and cyber victimization only (28.9%), and mutual violence (5.4%). Bullying was most strongly associated with the mutual violence class, suggesting a transformation of power from peer to romantic contexts. Social marginalization variables were associated with ADV patterns in different ways, highlighting the need to use a critical and anti-oppressive lens in ADV research and prevention initiatives.